Comparison between ultrasound and plain X-ray in evaluating the cause of shoulder pain - Salek, KM; Mannan, M; Chowdhury, AZ; Haque, MA; Kaiser, MS; Nabi, S; Ferdousee, RA; Paul, BK; Ahmed, SM; Khan, M; Begum, M (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jan;20(1):16-21 The abstract of this article is available on the PubMed website